The myofascial release and the treatment of tension headache induced by trigger points. - Sousa, Rayssilane Cardoso de; Matos, Ludmilla Karen Brandão Lima de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The presence of trigger points (TP) characterize the myofascial pain syndrome, which is associated with the Tension-Type Headaches (TTH) when the TP’s are located in the muscles of the head and neck, whose pattern of referred pain is propagated to certain regions of the head. In this context, the myofascial release (MR) has fundamental techniques for disabling TP’s and its symptoms. Objective: To verify the effects of myofascial release (MR) in the treatment of TTH induced to TP’s. Method: This study received approval from the Human Research Ethics Committee of a private college in Teresina-PI (No. 193 142). It is a series of cases report, of analytical nature with quantitative and qualitative approach. The sample was constituted by nine subjects with 42.67 ± 6.84 years, selected through a selecting form. They were evaluated before and after the treatment by means of an evaluation form (weight, height, goniometry cervical spine and visual analog pain scale - VAS) and the SF-36 Questionnaires. Was applied a protocol of physical therapy treatment with MR techniques, two times a week, 16 sessions. Analyzed variables: intensity of pain, range of movement (ROM) of the cervical spine and quality of life. Data were analyzed using parametric test “t” of Student, with significance level of p ≤ 0.05. Results: Data were reported in tables and graphs showing significant results. There was an increase of cervical spine ROM, reduced intensity of pain (VAS) and improves the quality of life of participants (SF-36 Questionnaire). Conclusion: The conclusion is that the protocol of physical therapy treatment with MR techniques showed significant results in the treatment of TTH.